Tools of business process modelling - Berecz, Patrícia (Acta Agraria Debreceniensis, 2009)
All companies have business processes, regardless of the size or the industry in which they operate. Both executive and operational managers need insight into software-based business processes and their performance for that transforming business workflows by modeling, simulating, optimizing, and publishing processes and defining business rules. I would like to introduce what kind of possibility the companies have got, when they want to model their business process. I choose the ARIS system from software market. I sketch out the function of ARIS system, and his application possibility. At last I present the best known diagram by means of some practical example.